2012
DOI: 10.1038/nnano.2012.90
|View full text |Cite|
|
Sign up to set email alerts
|

Magnetoferritin nanoparticles for targeting and visualizing tumour tissues

Abstract: Engineered nanoparticles have been used to provide diagnostic, therapeutic and prognostic information about the status of disease. Nanoparticles developed for these purposes are typically modified with targeting ligands (such as antibodies, peptides or small molecules) or contrast agents using complicated processes and expensive reagents. Moreover, this approach can lead to an excess of ligands on the nanoparticle surface, and this causes non-specific binding and aggregation of nanoparticles, which decreases d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
407
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 645 publications
(419 citation statements)
references
References 31 publications
10
407
1
1
Order By: Relevance
“…By using the intrinsic tumor-targeting properties of HFn, we recently reported that iron-encapsulated HFn NPs specifically target and visualize tumor tissues without the use of additional targeting ligands or signal molecules (17). In the present study, we loaded HFn nanocage with doxorubicin (Dox) for tumor-specific drug delivery.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…By using the intrinsic tumor-targeting properties of HFn, we recently reported that iron-encapsulated HFn NPs specifically target and visualize tumor tissues without the use of additional targeting ligands or signal molecules (17). In the present study, we loaded HFn nanocage with doxorubicin (Dox) for tumor-specific drug delivery.…”
mentioning
confidence: 95%
“…In the present study, we loaded HFn nanocage with doxorubicin (Dox) for tumor-specific drug delivery. HFn nanocages can encapsulate large amounts of foreign molecules (18)(19)(20)(21)(22)(23)(24), bind specifically to tumor cells that overexpress TfR1 (17), and should be able to efficiently deliver high doses of therapeutic drugs to tumors. In particular, natural HFn nanocarriers are expected to possess an outstanding biocompatibility and safety profile, because they exist naturally in the human body and are composed of nontoxic elements that therefore would not activate inflammatory or immunological responses (25).…”
mentioning
confidence: 99%
“…[ 12,13 ] The unique architecture of AFt provides two interfaces: the outer surface of AFt can be modifi ed chemically or genetically with functional motifs [ 14 ] and the internal cavity can be used to encapsulate pharmaceutical agents such as anticancer drugs, magnetic resonance imaging (MRI), and fl uorescent imaging agents. [ 6,9,15,16 ] Recently, selective targeting and cargo delivery with heavy chain apoferritin (H-AFt) was demonstrated both in vitro [ 17 ] and in vivo. [ 18 ] Gefi tinib ("Iressa," ZD1839) is an orally active, epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor.…”
mentioning
confidence: 99%
“…For example, magnetic Fe 3 O 4 75) 41,[84][85][86][87] for magnetic resonance imaging, 32,46) and even as the core of a magnonic device. 88) In analogy, Co(O)OH 89) 91) Many metal hydroxide NPs can be grown from the respective metal ion without an oxidizer.…”
Section: Apoferritinmentioning
confidence: 99%